The Effect of Planting Density and Supports on the Seed Yield of Mucuna cochinchinensis - A. H., Ridzwan; Hoe, C. H. (1982)
Mucuna cochinchinensis was planted for seed production using six planting systems. These comprised combinations of two planting distances; 1. 0 m x 1.0 m and 2.0 m x 2.0 m with three types of supports; no support, individual pole support for each plant or the wire-trellis type of support. Plants using either type of support outyielded the seed production from plants which received no support. Mean yield of normal seeds for unsupported plants, plants with individual support and plants with the wire trellis type of support were 76,677 and 736 kg/ha respectively. The lower yield of normal seeds from unsupported plants resulted from a combination of a lower total seed yield and a higher percentage of rotten seeds. Rotten seeds in unsupported plants comprised 68 percent of total seed yield compared to 38 percent and 33 percent for individually supported and wire-trellis supported plants respectively. Differences between the two types of supports were not significant. Planting distance did not have a significant effect on seed yield. However, for plants without any support there was a higher percentage of ;otten seeds (78%) for the more closely spaced plants than for plants planted at the wider spacing (54%).